EVALUASI DIKLAT ASN MODEL KIRKPATRICK (STUDI KASUS PELATIHAN EFFECTIVE NEGOTIATION SKILL BALAI DIKLAT KEUANGAN MAKASSAR) - Iskandar, Azwar (LPPM Universitas Terbuka, 2019)
This research was conducted with the aim of: (i) evaluating the trainees’s satisfaction on trainers and training performance; (ii) evaluating  the implementation of training results in their work units; (iii) evaluating the impact of training on trainee’s and/or unit performance; and (iv) identifying the constraints that hinders the training results to support the improvement of alumni competency and performance. Kirkpatrick's Evaluation Model was employed, and data was collected using questionnaires and interviews as well as descriptive statistical analysis techniques. The findings reveals that; (i) the overall aspects of training implementation were considered ‘very good’ by the participants, even though did not yet meet their level of expectation. The teacher however, indicates that the overall aspects of training have been able to meet the expectations of participants; (ii) the Effective Negotiation Skills training improved alumni competency after returning to work. This can be seen from the average value of the total perceptions of alumni respondents related to changes in competence after participating in training as much as 8.34 (on a scale of 1-10). Paired sample t-test analysis also showed a significant influence indicating improvement of alumni competency, especially in negotiating with the stakeholders; (iii) the results of training significantly have positive impacts on trainee’s and/or unit performance. This can be seen from the average total of alumni perception on impacts of 4.12 (high) in scale of 1-5 where 1 is very low and 5 is very high) scale. Majority of alumni feel that its positive impacts indicated by increasing of negotiation capability to stakeholders; (iv) The biggest obstacle experienced by alumni in applying knowledge obtained from the training in the workplace is different language, culture, and character, which posed  difficulty for them to negotiate and communicate work unit tasks and target performance. Penelitian ini  dilaksanakan dengan tujuan: (i) mengevaluasi kepuasan peserta diklat terhadap pengajar dan penyelenggaraan diklat; (ii) mengevaluasi implementasi hasil diklat setelah kembali ke unit kerja; (iii) mengevaluasi dampak hasil diklat dalam meningkatkan kinerja alumni diklat dan/atau unit kerja; dan (iv) mengidentifikasi kendala yang menghambat penerapan hasil pelatihan. Model Evaluasi Kirkpatrick digunakan dalam penelitian ini, dan data dikumpulkan dengan menggunakan kuesioner dan wawancara serta teknik analisis statistik deskriptif. Temuan mengungkapkan bahwa (i) keseluruhan aspek evaluasi penyelenggaraan dinilai oleh peserta dengan kategori Sangat Baik meskipun belum dapat memenuhi tingkat harapan dari peserta yang ditunjukkan dengan angka rata-rata di bawah 100%. Di sisi lain, keseluruhan aspek evaluasi pengajar telah dapat memenuhi harapan dari peserta; (ii) pelatihan mampu meningkatkan kompetensi alumni dalam mendukung pekerjaan alumni setelah kembali ke unit kerja. Hal ini terlihat dari nilai rata-rata total persepsi responden alumni terkait perubahan kompetensi setelah mengikuti diklat sebesar 8,34 (dari skala 1-10). Hasil uji-t berpasangan menunjukkan hal yang sama bahwa program pelatihanyang dilakukan berhasil dan memiliki pengaruh yang signifikan dalam peningkatan kompetensi alumni; (iii) hasil pelatihan memberikan dampak terhadap kinerja alumni dan/atau unit kerja alumni dengan nilai rata-rata tingkat dampak positif bagi kinerja individu dan/atau unit kerja dengan kategori tinggi; (iv) kendala terbesar yang dialami oleh alumni dalam menerapkan pengetahuan yang diperoleh dari pelatihan di tempat kerja adalah perbedaan bahasa, budaya, dan karakter, yang menimbulkan kesulitan ketika  melakukan negosiasi dan komunikasi tentang tugas dan target kinerja unit.